2023
DOI: 10.3390/jpm13010132
|View full text |Cite
|
Sign up to set email alerts
|

Non-Typical Clinical Presentation of COVID-19 Patients in Association with Disease Severity and Length of Hospital Stay

Abstract: Background: This study aimed to investigate the incidence of non-typical symptoms in ambulatory patients with mild-to-moderate COVID-19 infection and their potential association with disease progression. Materials and methods: Data on the symptomatology of COVID-19 patients presenting to the fast-track emergency department were collected between March 2020 and March 2021. Fever, cough, shortness of breath, and fatigue-weakness were defined as “typical” symptoms, whereas all other symptoms such as nasal congest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Similar data were reported from Asia and Australia [ 2 4 ]. As things were not complicated enough, numerous studies (mostly retrospective) and meta-analyses confirmed the GI involvement in COVID-19 [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar data were reported from Asia and Australia [ 2 4 ]. As things were not complicated enough, numerous studies (mostly retrospective) and meta-analyses confirmed the GI involvement in COVID-19 [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%